УСЛОВИЯ ВОЗНИКНОВЕНИЯ И РОСТА ТРЕЩИН В РОТОРЕ ТУРБОГЕНЕРАТОРА ВСЛЕДСТВИЕ ЭЛЕКТРОДИНАМИЧЕСКИХ ВОЗДЕЙСТВИЙ В АНОРМАЛЬНЫХ РЕЖИМАХ - Tитко , A.И.; Васьковский, Ю.Н.; Ахременко , В.Л. (Інститут електродинаміки НАН України, Київ, 2012)
It is shown, that short-term abnormal modes cause sharp increase in mechanical pressure in local zones of a rotor of a turbogenerator that can conduct to occurrence in a rotor of cracks. At the certain parameters growth of cracks under normal conditions operation begins. Growth rate of cracks depends on characteristics of metal of a rotor and the environment of cooling. By the example of turbogenerator TГB-300-2 it is shown, that maximum permissible time of his operation after an abnormal mode should not exceed 4000 hours, and the careful control of a condition of a material of a rotor is necessary for maintenance of his further operation. References 6, table 1, figures 2.